LUNAR MOON PHASE TERHADAP TANGKAPAN PERSATUAN UPAYA IKAN KEMBUNG (Rastrelliger spp, Bleeker, 1851) DI PULAU DAMAR, KEPULAUAN SERIBU - Aziz, K. A.; Butet, N.A; Pujiastuti, D. (Fakultas Perikanan dan Kelautan Universitas Riau, 2009)
Ones of information that needed on fisheries resources management isevalute catch per unit effort daily, montly, and annually. Daily of CPUEinfluenced of moon phase, and montly of CPUE might cause of fishing season.The CPUE research of Kembung Fish (Restrelliger spp) in Thousand Island is forstudy of lunar moon influence to cacth and season. This research done at june2006 to februari 2007 at Panggang-Pramuka Island, Kelapa Island, Tidung Island,Lancang Island, and Damar Island. Result of study knowns that Restrelliger spcatch on the peak solar moon less than a few day before and after solar moonpeak. Fishing season in Damar and Panggang-Pramuka Island shown on August-October, and Lancang, Kelapa, also Tidung Island on June-September. OnDecember, a part of Kembung fish migrate to east of damal island.